The PEG-coated collagen patch Hemopatch® for hemostasis and dural sealing in neurosurgery - Rossmann, Jakob; Antunes, Apio C. M.; Broc, Guy G.; Chan, Danny T. M.; Chen, Se-Yi; Dea, Nicolas; Fairhall, Jacob; de Andrés Guijarro, Pablo; Montano, Nicola; Schebesch, Karl-Michael; Timothy, Jake; Yerramneni, Vamsi Krishna (Frontiers in Surgery, 2025)
BackgroundPostoperative cerebrospinal fluid (CSF) leakage and bleeding are major postoperative complications that increase healthcare system costs. The use of Hemopatch® Sealing Hemostat has been shown to reduce the incidence of such postoperative complications. This technical report aims to provide neurosurgeons with the best recommendations for the effective use of Hemopatch® as a hemostatic and dural sealant in cranial and spinal procedures.Material and methodsThe clinical experiences of 10 neurosurgeons from around the world regarding the use of Hemopatch® were evaluated using an online survey, followed by a hands-on preclinical workshop on adult pigs, which concluded with an in-depth discussion about the use of the patch.ResultsThe survey results provide an overview of how and when experts use different types of dural repair materials, including decision-making factors. During the workshop, Hemopatch® presented excellent tissue adherence on all evaluated defects. The new configuration of the patch showed improved tissue adherence, less curling of the patch, and easier removal of the gauze used for compression. Experts recommend using patches that overlap the defect for ≥1 cm. When closing defects that do not allow for a dried application site, Hemopatch® can be put on a dry gauze, which can be bent into a U-shape. This allows better targeting of the application site and enables immediate compression upon placement.ConclusionThe results provide information to improve the hands-on use of Hemopatch® as a dural sealant, therefore reducing the risk of postoperative complications such as CSF leaks, eventually reducing healthcare system costs.